Implementasi Metode Demonstrasi dalam Peningkatan Prestasi Belajar Siswa Kelas XI MIPA B pada Bidang Studi Bahasa Jawa di SMA Al Azhar Menganti Gresik - Muhammad Abdullah Faqih (LP3M STITNU AL HIKMAH MOJOKERTO, 2021)
The purpose of this study is to determine the application of the demonstration method in improving student achievement. Data obtained from interviews, observations and documentation. The research subjects were students of class XI MIPA SMA Al Azhar Menganti Gresik. Based on the results of observations, obtained data on the pre-action of class completeness. This is evidenced from the results of the implementation of the first cycle of 71 and in the second cycle it became 80.29 above the indicators of learning success. Based on these data, the researcher concludes that the demonstration method can improve student achievement in the field of Javanese language studies.